EVALUATION OF MAXILLARY SINUS VOLUME IN ADULT VIETNAMESE USING COMPUTED TOMOGRAPHY (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the dimensions of the maxillary sinus measured on maxillofacial computed tomography (CT) scans and estimate the volume of the maxillary sinus. This study aims to evaluate the differences in maxillary sinus size between males and females, as well as between the left and right sides of the normal maxillary sinus in Vietnamese adults.Materials and methods: This is a cross-sectional, descriptive case series study. A total of 196 maxillary sinuses were examined using maxillofacial computed tomography (CT) scans from 98 Vietnamese individuals aged 18 and older, with no related sinonasal pathology, conducted at Can Tho University of Medicine and Pharmacy Hospital. The vertical, transverse, and anteroposterior diameters of the maxillary sinus were measured using the bone window on non-contrast maxillofacial CT scans. The sinus volume was estimated using a formula based on these measurements. Statistical analysis was performed to compare differences in the obtained parameters.Results: The mean age of the study sample was 47.02 ± 12.076 years. The smallest measured sinus volume was 6.17 cm³, the largest was 40.62 cm³, and the average volume was 22.4672 ± 7.651 cm³. The maxillary sinus volume in males was larger than in females, with a statistically significant difference (p = 0.04 < 0.05). No statistically significant difference was found in the maxillary sinus volume between the right and left sides.Conclusion: Using computed tomography to evaluate maxillary sinus volume provides valuable insights into the morphological characteristics of the Vietnamese population, enhancing knowledge for clinical and anthropological applications.